Disentangling the Coefficient of Relative Risk Aversion From the Elasticity of Intertemporal Substitution: An Irrelevance Result. - Kocherlakota, Narayana R (Journal of Finance, 1990)
For homothetic time and state separable preferences, the coefficient of relative risk aversion is equal to the reciprocal of the elasticity of intertemporal substitution. This paper shows that, when the growth rate of consumption is independent and identically distributed, asset pricing models based upon preferences in which the coefficient of relative risk aversion and the elasticity of intertemporal substitution are no longer linked do not have more explanatory power. Further, in these stochastic environments, estimates of the coefficient of relative risk aversion in the standard preferences are measures of the true coefficient of relative risk aversion and not the elasticity of intertemporal substitutions. These results are fairly accurate descriptions of economies calibrated using United States annual data.